Interaction Between Language and Culture - Matyakubov Zohid Mo’minbayevich (Genius Publishing Group, 2023)
This article provides information about the words used in Linguistics and the interaction between language and culture.
Keywords: Linguistics; culture; linguistic culture; anthropological research